«Nurly Jol» and national policy (Journal of Philosophy Culture and Political Science, 2015)
In the article the political analysis of concepts such as nationality, ethnicity,nation, ethnic group, diaspora, nationality, as well as the differentconcepts of ethno-political community and national interests. The importanceof national unity in achieving the goals and targets set out in theletter Elbasy NA Nazarbayev «Nurly Jol – way of the future.» Social cohesionand political stability in Kazakhstan is considered as the main factorsof development. The paper is also proved by the fact that the conversionof the people of the country into a single ethno-political community andnational actions are zologom successful implementation of strategic plansand the protection of national interests.
Keywords: ethnic policies; state; national interest; nation; diaspora; «Nurly Jol» Elbasy; democracy; social harmony; political stability; the fate of the nation.